1973
DOI: 10.3181/00379727-142-37119
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Endogenous Renin With Exogenous Renin Substrate Within the Isolated Perfused Rat Kidney

Abstract: In previous experiments on the isolated rabbit kidney perfused with a medium free from renin substrate (RS) we have shown that addition of RS resulted in an increase in renal vascular resistance (RVR) , glomerular filtration rate (GFR), and filtration fraction (FF) ( 1 ) . Since these experiments were performed in a recirculating perfusion system, it was not possible to decide whether renin had reacted with its substrate within the kidney or outside of it. To obtain better information on the site of enzymesubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…However, 10 min after the infusion of RS had been stopped, RPF had not returned to its previous value. This observation is consistent with our results in isolated rat kidneys perfused at constant flow (Hofbauer et al, 1973) and is suggestive of differences in action between infused and intrarenally released AI.…”
Section: Discussionsupporting
confidence: 93%
“…However, 10 min after the infusion of RS had been stopped, RPF had not returned to its previous value. This observation is consistent with our results in isolated rat kidneys perfused at constant flow (Hofbauer et al, 1973) and is suggestive of differences in action between infused and intrarenally released AI.…”
Section: Discussionsupporting
confidence: 93%
“…First, the present study demonstrates that the renin-angiotensin system is not physio logically intact in the isolated perfused rat kidney system. While previous studies have demonstrated an absence of renin substrate in artificial perfusion media [13], there have been no previous determinations of angio tensin converting enzyme. Our results dem onstrate clearly, for the first time, an ab sence of converting enzyme in the perfusate and a failure of release of this enzyme into the perfusate with time.…”
Section: Discussionmentioning
confidence: 95%
“…Previous evaluations of the dynamics of renin release with the recirculating perfused kidney technique have assumed that renin release is subtended by a linear function [8][9][10][11][12][13][20][21][22][23][24][25]. Furthermore, renal function was not examined concomitantly, rendering the interpretation of such renin data difficult.…”
Section: Introductionmentioning
confidence: 99%
“…A crude preparation of rat plasma renin substrate induced a dose-dependent vasoconstriction (Hofbauer et al, 1973a). This effect could not be inhibited by SQ 20 881 (Hofbauer et al, 1973b), which suggests that no conversion of A1 to A11 was involved in the production of the effect.…”
Section: Intrarenal Formation Of Aiimentioning
confidence: 89%